X+2Y看成一项,3Z看成另一项,用平方差公式展开……
(X+2Y+3Z)(X+2Y-3Z)简便方法怎么算
1个回答
相关问题
-
(x+2y-z)(x-2y-z) 简便方法
-
5x y-2z=17 2x-3y 7z=8 6x 2=3(y 6z)怎么算
-
证明:(y+z-2x)3+(z+x-2y)3+(x+y-2z)3=3(y+z-2x)(z+x-2y)(x+y-2z).
-
x^2(y+z)+y^2(z+x)+z^2(x+y)-(x^3+y^3+z^3)-2xyz
-
化简 [x^3(y^2-z^2)+y^3(z^2-x^2)+z^3(x^2-y^2)]/[x^3(y-z)+y^2(z-
-
因式分解X2(Y+Z)+Y2(Z+X)+Z2(X+Y)-(X3+Y3+Z3)-2XYZ
-
设x,y,z为正数,证明:2(x^3+y^3+z^3)≥(x^2)(y+z)+(y^2)(x+z)+(z^2)(x+y)
-
x+y+z=6,3x-y-4z=-11,2x+3y_2z=2怎么解
-
一.{x+2y+3z=14 2x-y-z=-3 3x+y+z=8 二.{3X-2Y-2Z=3 2X+2Y+3Z=12 X
-
x+2z=3 x+y+z=2 2x+y=2 3x-y-4z=5 2y+z=7 2x+3y-2z=0